M. al-Ŷābirī, and the debate about the arabic reason - Zurghani, Hussein O. (Anaquel de Estudios Árabes, 2004)
Muhammad ‛Ābid al-Ŷābirī (born 1935) is the most recognized contemporary Moroccan philosopher. His thesis asserting a cleavage between Western and Eastern Arabic thought has raised a wide discussion. The article analyses how al-Ŷābirī interpretates Averroes’ work The conclusive treatise on the coincidence of philosophy and revealed religion, which he has edited and fore worded with a long essay. Al-Ŷābirī insists in the cleavage inside the Islamic thought, between a Western direction in favour of reason and an Eastern in favour of mysticism. I take into consideration the various reactions to the thesis among contemporary Arab thinkers, and I express my view sustaining the continuity inherent Western and Eastern Arabic thought.
Keywords: Muhhammad ‛ Ā bid al-Ŷ ā birī Averroes; Contemporary Arabic thought